Wheat Crop-Share Leases in Central Kansas 1974-1993 - Warmann, Gerald W. (My University, 1995)
This publication shares information about wheat crop-share leases in central Kansas from 1974 to 1993.
MF2170_1995_11
Keywords: MF2170; Crops; Economics; MF